Career paths of selected interior design graduates of the University of the Philippines-Diliman - Tablac, Aileen Karla D. (UP College of Home Economics, 2012)
The study sought to identify the career paths of selected interior design graduates of the University of the Philippines-Diliman from the year 1995 to 2001, and to examine the factors affecting their choices as well as the implications of the interior design education to these choices. A quantitative approach that employed the use of survey was the research design of the study. Twenty three respondents participated, and they were selected through purposive and snowball sampling. The instrument used to gather data was a survey questionnaire. The career paths of the respondents were generally inclined to jobs related to interior design. Results of the study showed that in terms of their current jobs, 11 of the 23 respondents took on allied jobs while the rest were engaged in non-allied jobs. Twelve of the 23 respondents had part time-jobs which were mostly related to interior design. Also, most of the respondents pursued allied jobs before engaging in non-allied jobs. In general, the factor that the respondents considered most influential to their choice of current, part-time and past jobs was learning experiences. Overall, the respondents deemed their interior design education influential to their choice of jobs. They considered their learning experiences as a significant factor in their decision to pursue certain jobs. Results revealed that the graduates were able to utilize the knowledge, skills and competencies they acquired from their education in the jobs they took on, whether allied or non-allied.